Strong oscillations for second order nonlinear functional differential equations - Jurang Yan (International Journal of Mathematics and Mathematical Sciences)
In this paper, we establish some strongly oscillation theorems for nonlinear second order functional differential equationx″(t)+p(t)f(x(t),x(g(t)))=0without assuming that g(t) is retarded or advanced.